2005
DOI: 10.1038/modpathol.3800399
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and prognostic significance of microsatellite alterations in young patients with bladder cancer

Abstract: Mutations in microsatellite sequences are a hallmark of neoplastic transformation and have been reported in the majority of human cancers. Conflicting results have been reported on the role of microsatellite alterations in bladder tumorigenesis and it has been suggested that they might be mainly involved in the development of bladder cancers in young patients. In this study, DNA was extracted from laser-microdissected samples of 51 superficial papillary bladder urothelial carcinomas arising in young patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 21 publications
0
14
1
Order By: Relevance
“…A number of studies have examined the role of microsatellite instability in the pathogenesis of urothelial neoplasms in young patients. These studies have reported conflicting results though, with some showing significant microsatellite instability [3, 23] and others showing minimal microsatellite instability [6, 7]. The collected findings of these studies suggest a role for additional research into the unique genetic mechanisms associated with urothelial neoplasms in young patients.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have examined the role of microsatellite instability in the pathogenesis of urothelial neoplasms in young patients. These studies have reported conflicting results though, with some showing significant microsatellite instability [3, 23] and others showing minimal microsatellite instability [6, 7]. The collected findings of these studies suggest a role for additional research into the unique genetic mechanisms associated with urothelial neoplasms in young patients.…”
Section: Discussionmentioning
confidence: 99%
“…Both contradicted 2 earlier studies which reported high MSI (100%) in bladder cancer from patients aged 35 to 55 years 34 and frequent microsatellite alterations (100%) in superficial bladder urothelial carcinomas from patients aged 20 to 45 years. 33 It was suggested that use of large number (22 panels) of dinucleotide markers may possibly explain the higher MSI detected. [32][33][34] Of note, the patient cohorts in those 2 studies were much older than in the study by Wild et al 31 (4 to 19 y) and also had higher number of invasive and grade 3 tumors.…”
Section: Molecular Featuresmentioning
confidence: 99%
“…33 It was suggested that use of large number (22 panels) of dinucleotide markers may possibly explain the higher MSI detected. [32][33][34] Of note, the patient cohorts in those 2 studies were much older than in the study by Wild et al 31 (4 to 19 y) and also had higher number of invasive and grade 3 tumors. The study by Migaldi et al 33 showed microsatellite alteration to be associated with reduced risk of tumor recurrence and disease progression, but this was only shown in the univariate analysis.…”
Section: Molecular Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Young patients tend to present more frequently with noninvasive low-grade tumors, as in this case being presented. 2,3 Case Report A 17-year-old female, gravida 1, para 0, presented to the emergency room with low back pain and spotting in her first trimester. An early obstetrical sonogram was ordered to evaluate the pregnancy.…”
mentioning
confidence: 99%